GEOTECHNICAL HAZARDS IN BANGKOK - PRESENT AND FUTURE - S. Shibuya; S. B. Tamrakar; W. Manakul (International Association of Lowland Technology, 2003)
Geotechnical hazards in Bangkok, the capital of Thailand, are cited with reference to floods, land subsidence and earthquakes, bearing the characteristic subsoil conditions in mind. First, geotechnical engineering works concerning the implementation of flood protection schemes are briefly outlined. Second, the cause of land subsidence, i.e., the drawdown of pore pressures in clay layer induced by water pumping in the aquifer, together with the current situations are described by showing the results of geotechnical site investigation performed recently. Finally, a risk of seismic hazard in Bangkok is roused by referring to a statement that “the surficial geologic setting at Bangkok is similar to the setting of Mexico City, and hence Bangkok, by analogy, appears to be susceptible to the same type of soil amplification of ground motions (Warnitchai et al. 2000)”.